Find expert advice and community support for all your questions on IDNLearn.com. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Sure! Let's start with the step-by-step solution for each part in Q4.
### Q4.1:
a) Evaluate the integral:
[tex]\[ \int \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 dx \][/tex]
First, simplify the integrand:
[tex]\[ \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 = \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right) \cdot \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right) \][/tex]
[tex]\[ = \frac{(\sqrt{x+2})^2}{(\sqrt{x})^2} = \frac{x+2}{x} = 1 + \frac{2}{x} \][/tex]
Now, rewrite the integral:
[tex]\[ \int \left( 1 + \frac{2}{x} \right) dx \][/tex]
[tex]\[ = \int 1 \, dx + \int \frac{2}{x} \, dx \][/tex]
Evaluate each term separately:
[tex]\[ \int 1 \, dx = x \][/tex]
[tex]\[ \int \frac{2}{x} \, dx = 2 \ln |x| \][/tex]
Combining the results, we get:
[tex]\[ x + 2 \ln |x| + C \][/tex]
Therefore,
[tex]\[ \int \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 dx = x + 2 \ln |x| + C \][/tex]
b) Evaluate the integral:
[tex]\[ \int \sin x (\cos x + 3) dx \][/tex]
First, distribute [tex]\(\sin x\)[/tex]:
[tex]\[ \int \sin x \cos x \, dx + \int 3 \sin x \, dx \][/tex]
Now, we will use substitution for each integral:
For [tex]\(\int \sin x \cos x \, dx\)[/tex], set [tex]\(u = \cos x\)[/tex]:
[tex]\[ \frac{du}{dx} = -\sin x \][/tex]
[tex]\[ du = -\sin x \, dx \][/tex]
[tex]\[ dx = -\frac{du}{\sin x} \][/tex]
Substitute:
[tex]\[ \int \sin x \cos x \, dx = \int -\cos x \, du = -\int u \, du = -\frac{u^2}{2} + C_1 = -\frac{\cos^2 x}{2} + C_1 \][/tex]
For [tex]\(\int 3 \sin x \, dx\)[/tex], we know:
[tex]\[ \int 3 \sin x \, dx = -3 \cos x + C_2 \][/tex]
Combining both results, we get:
[tex]\[ \int \sin x (\cos x + 3) dx = -\frac{\cos^2 x}{2} - 3 \cos x + C \][/tex]
### Q4.2:
a) Evaluate the integral:
[tex]\[ \int \left( \frac{1}{4 + x^2} \right) dx \][/tex]
This is a standard integral that can be recognized as a form of the arctangent function. Specifically:
[tex]\[ \int \frac{1}{a^2 + x^2} dx = \frac{1}{a} \arctan\left( \frac{x}{a} \right) + C \][/tex]
For our case, [tex]\(a = 2\)[/tex]:
[tex]\[ \int \frac{1}{4 + x^2} dx = \frac{1}{2} \arctan\left( \frac{x}{2} \right) + C \][/tex]
b) Evaluate the integral:
[tex]\[ \int_0^2 \frac{(x-2)}{(x+3)(x-4)} dx \][/tex]
To evaluate this improper integral, use partial fraction decomposition. Assume:
[tex]\[ \frac{x-2}{(x+3)(x-4)} = \frac{A}{x+3} + \frac{B}{x-4} \][/tex]
Multiply both sides by [tex]\((x+3)(x-4)\)[/tex]:
[tex]\[ x - 2 = A(x-4) + B(x+3) \][/tex]
Now, solve for [tex]\(A\)[/tex] and [tex]\(B\)[/tex] by substituting convenient values of [tex]\(x\)[/tex]:
- Let [tex]\(x = 4\)[/tex]:
[tex]\[ 4 - 2 = A(4-4) + B(4+3) \][/tex]
[tex]\[ 2 = 7B \][/tex]
[tex]\[ B = \frac{2}{7} \][/tex]
- Let [tex]\(x = -3\)[/tex]:
[tex]\[ -3 - 2 = A(-3-4) + B(-3+3) \][/tex]
[tex]\[ -5 = -7A \][/tex]
[tex]\[ A = \frac{5}{7} \][/tex]
So the partial fraction decomposition is:
[tex]\[ \frac{x-2}{(x+3)(x-4)} = \frac{5/7}{x+3} + \frac{2/7}{x-4} \][/tex]
Rewrite the original integral:
[tex]\[ \int_0^2 \left( \frac{5/7}{x+3} + \frac{2/7}{x-4} \right) dx \][/tex]
[tex]\[ = \frac{5}{7} \int_0^2 \frac{1}{x+3} dx + \frac{2}{7} \int_0^2 \frac{1}{x-4} dx \][/tex]
Evaluate each integral separately:
For [tex]\(\int_0^2 \frac{1}{x+3} dx\)[/tex], set [tex]\(u = x + 3\)[/tex]:
[tex]\[ du = dx \][/tex]
[tex]\[ \int_3^5 \frac{1}{u} du = \ln |u| \Big|_3^5 \][/tex]
[tex]\[ = \ln 5 - \ln 3 = \ln \frac{5}{3} \][/tex]
For [tex]\(\int_0^2 \frac{1}{x-4} dx\)[/tex], set [tex]\(v = x - 4\)[/tex]:
[tex]\[ dv = dx \][/tex]
[tex]\[ \int_{-4}^{-2} \frac{1}{v} dv = \ln |v| \Big|_{-4}^{-2} \][/tex]
[tex]\[ = \ln (-2) - \ln (-4) = \ln \left( \frac{-2}{-4} \right) = \ln \frac{1}{2} = -\ln 2 \][/tex]
Combine the results and remember the integral bounds need to match (since one part becomes negative log):
[tex]\[ \frac{5}{7} \ln \frac{5}{3} + \frac{2}{7} (-\ln 2) \][/tex]
[tex]\[ = \frac{5}{7} \ln \frac{5}{3} - \frac{2}{7} \ln 2 \][/tex]
Therefore:
[tex]\[ \int_0^2 \frac{(x-2)}{(x+3)(x-4)} dx = \frac{5}{7} \ln \frac{5}{3} - \frac{2}{7} \ln 2 \][/tex]
### Q4.1:
a) Evaluate the integral:
[tex]\[ \int \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 dx \][/tex]
First, simplify the integrand:
[tex]\[ \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 = \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right) \cdot \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right) \][/tex]
[tex]\[ = \frac{(\sqrt{x+2})^2}{(\sqrt{x})^2} = \frac{x+2}{x} = 1 + \frac{2}{x} \][/tex]
Now, rewrite the integral:
[tex]\[ \int \left( 1 + \frac{2}{x} \right) dx \][/tex]
[tex]\[ = \int 1 \, dx + \int \frac{2}{x} \, dx \][/tex]
Evaluate each term separately:
[tex]\[ \int 1 \, dx = x \][/tex]
[tex]\[ \int \frac{2}{x} \, dx = 2 \ln |x| \][/tex]
Combining the results, we get:
[tex]\[ x + 2 \ln |x| + C \][/tex]
Therefore,
[tex]\[ \int \left(\frac{\sqrt{x+2}}{\sqrt{x}}\right)^2 dx = x + 2 \ln |x| + C \][/tex]
b) Evaluate the integral:
[tex]\[ \int \sin x (\cos x + 3) dx \][/tex]
First, distribute [tex]\(\sin x\)[/tex]:
[tex]\[ \int \sin x \cos x \, dx + \int 3 \sin x \, dx \][/tex]
Now, we will use substitution for each integral:
For [tex]\(\int \sin x \cos x \, dx\)[/tex], set [tex]\(u = \cos x\)[/tex]:
[tex]\[ \frac{du}{dx} = -\sin x \][/tex]
[tex]\[ du = -\sin x \, dx \][/tex]
[tex]\[ dx = -\frac{du}{\sin x} \][/tex]
Substitute:
[tex]\[ \int \sin x \cos x \, dx = \int -\cos x \, du = -\int u \, du = -\frac{u^2}{2} + C_1 = -\frac{\cos^2 x}{2} + C_1 \][/tex]
For [tex]\(\int 3 \sin x \, dx\)[/tex], we know:
[tex]\[ \int 3 \sin x \, dx = -3 \cos x + C_2 \][/tex]
Combining both results, we get:
[tex]\[ \int \sin x (\cos x + 3) dx = -\frac{\cos^2 x}{2} - 3 \cos x + C \][/tex]
### Q4.2:
a) Evaluate the integral:
[tex]\[ \int \left( \frac{1}{4 + x^2} \right) dx \][/tex]
This is a standard integral that can be recognized as a form of the arctangent function. Specifically:
[tex]\[ \int \frac{1}{a^2 + x^2} dx = \frac{1}{a} \arctan\left( \frac{x}{a} \right) + C \][/tex]
For our case, [tex]\(a = 2\)[/tex]:
[tex]\[ \int \frac{1}{4 + x^2} dx = \frac{1}{2} \arctan\left( \frac{x}{2} \right) + C \][/tex]
b) Evaluate the integral:
[tex]\[ \int_0^2 \frac{(x-2)}{(x+3)(x-4)} dx \][/tex]
To evaluate this improper integral, use partial fraction decomposition. Assume:
[tex]\[ \frac{x-2}{(x+3)(x-4)} = \frac{A}{x+3} + \frac{B}{x-4} \][/tex]
Multiply both sides by [tex]\((x+3)(x-4)\)[/tex]:
[tex]\[ x - 2 = A(x-4) + B(x+3) \][/tex]
Now, solve for [tex]\(A\)[/tex] and [tex]\(B\)[/tex] by substituting convenient values of [tex]\(x\)[/tex]:
- Let [tex]\(x = 4\)[/tex]:
[tex]\[ 4 - 2 = A(4-4) + B(4+3) \][/tex]
[tex]\[ 2 = 7B \][/tex]
[tex]\[ B = \frac{2}{7} \][/tex]
- Let [tex]\(x = -3\)[/tex]:
[tex]\[ -3 - 2 = A(-3-4) + B(-3+3) \][/tex]
[tex]\[ -5 = -7A \][/tex]
[tex]\[ A = \frac{5}{7} \][/tex]
So the partial fraction decomposition is:
[tex]\[ \frac{x-2}{(x+3)(x-4)} = \frac{5/7}{x+3} + \frac{2/7}{x-4} \][/tex]
Rewrite the original integral:
[tex]\[ \int_0^2 \left( \frac{5/7}{x+3} + \frac{2/7}{x-4} \right) dx \][/tex]
[tex]\[ = \frac{5}{7} \int_0^2 \frac{1}{x+3} dx + \frac{2}{7} \int_0^2 \frac{1}{x-4} dx \][/tex]
Evaluate each integral separately:
For [tex]\(\int_0^2 \frac{1}{x+3} dx\)[/tex], set [tex]\(u = x + 3\)[/tex]:
[tex]\[ du = dx \][/tex]
[tex]\[ \int_3^5 \frac{1}{u} du = \ln |u| \Big|_3^5 \][/tex]
[tex]\[ = \ln 5 - \ln 3 = \ln \frac{5}{3} \][/tex]
For [tex]\(\int_0^2 \frac{1}{x-4} dx\)[/tex], set [tex]\(v = x - 4\)[/tex]:
[tex]\[ dv = dx \][/tex]
[tex]\[ \int_{-4}^{-2} \frac{1}{v} dv = \ln |v| \Big|_{-4}^{-2} \][/tex]
[tex]\[ = \ln (-2) - \ln (-4) = \ln \left( \frac{-2}{-4} \right) = \ln \frac{1}{2} = -\ln 2 \][/tex]
Combine the results and remember the integral bounds need to match (since one part becomes negative log):
[tex]\[ \frac{5}{7} \ln \frac{5}{3} + \frac{2}{7} (-\ln 2) \][/tex]
[tex]\[ = \frac{5}{7} \ln \frac{5}{3} - \frac{2}{7} \ln 2 \][/tex]
Therefore:
[tex]\[ \int_0^2 \frac{(x-2)}{(x+3)(x-4)} dx = \frac{5}{7} \ln \frac{5}{3} - \frac{2}{7} \ln 2 \][/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.